2020
DOI: 10.1523/eneuro.0448-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Hsc70 Ameliorates the Vesicle Recycling Defects Caused by Excess α-Synuclein at Synapses

Abstract: ␣-Synuclein overexpression and aggregation are linked to Parkinson's disease (PD), dementia with Lewy bodies (DLB), and several other neurodegenerative disorders. In addition to effects in the cell body, ␣-synuclein accumulation occurs at presynapses where the protein is normally localized. While it is generally agreed that excess ␣-synuclein impairs synaptic vesicle trafficking, the underlying mechanisms are unknown. We show here that acute introduction of excess human ␣-synuclein at a classic vertebrate syna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 94 publications
3
47
1
1
Order By: Relevance
“…Next, 2–3 cm segments of spinal cord were dissected and pinned ventral side up in a Sylgard-lined dish containing fresh, oxygenated Lamprey Ringer (100 mM NaCl, 2.1 mM KCl, 1.8 mM MgCl 2 , 4 mM glucose, 2 mM HEPES, 0.5 mM L-glutamine, 2.6 mM CaCl 2 , pH 7.4). Axonal microinjections were performed as previously described ( Medeiros et al, 2017 ; Walsh et al, 2018 ; Banks et al, 2020 ; Soll et al, 2020 ). Briefly, SEC fraction 12 containing human α-synuclein was diluted in lamprey internal solution (180 mM KCl and 10 mM HEPES K+; pH 7.4) to a pipet concentration of 800 nM and subsequently loaded into glass microelectrodes (20–25 MΩ) for microinjection into giant RS axons.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, 2–3 cm segments of spinal cord were dissected and pinned ventral side up in a Sylgard-lined dish containing fresh, oxygenated Lamprey Ringer (100 mM NaCl, 2.1 mM KCl, 1.8 mM MgCl 2 , 4 mM glucose, 2 mM HEPES, 0.5 mM L-glutamine, 2.6 mM CaCl 2 , pH 7.4). Axonal microinjections were performed as previously described ( Medeiros et al, 2017 ; Walsh et al, 2018 ; Banks et al, 2020 ; Soll et al, 2020 ). Briefly, SEC fraction 12 containing human α-synuclein was diluted in lamprey internal solution (180 mM KCl and 10 mM HEPES K+; pH 7.4) to a pipet concentration of 800 nM and subsequently loaded into glass microelectrodes (20–25 MΩ) for microinjection into giant RS axons.…”
Section: Methodsmentioning
confidence: 99%
“…Using the lamprey giant reticulospinal synapse as a model, our lab previously showed that acute introduction of excess recombinant monomeric or dimeric human α-synuclein led to a loss of synaptic vesicles, expansion of the plasma membrane, and increased numbers of clathrin-coated structures and other endocytic intermediates, indicating impaired synaptic vesicle recycling ( Busch et al, 2014 ; Medeiros et al, 2017 ; Banks et al, 2020 ). An inhibition of endocytosis, but not exocytosis, was also reported at mammalian calyx of Held synapses dialyzed with recombinant human α-synuclein ( Xu et al, 2016 ; Eguchi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [42] estimated the concentration of -syn in the presynaptic terminal to be 3.5 M. Monomeric -syn is most likely degraded in proteasomes [43,51].…”
Section: Finding Values Of Kinetic Constants By Least Square Regressionmentioning
confidence: 99%